2009
DOI: 10.1093/jac/dkp345
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of methicillin-resistant Staphylococcus aureus (MRSA) among residents of nursing homes in Belgium

Abstract: A high prevalence of MRSA carriage in NH residents was associated with hospital care, co-morbidities and less-developed coordination of institutional care. The predominant MRSA strains from NH residents and hospitalized patients of the same area were identical. Strengthening and coordination of MRSA surveillance and control activities are warranted within and between NHs and hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 33 publications
9
48
1
Order By: Relevance
“…Drug-resistant bacterial infection treatment has been stimulated by investigations on natural compounds as alternative medicine (Abu-Shanab et al, 2004;Adwan and Mhanna, 2008;Denis et al, 2009). In the present study, analyses of growth inhibition activity performed by using the well diffusion method showed that all the tested plants, which are commonly used by traditional medical practitioners, exhibited moderate activity against clinical isolates of bacterial strains at extract concentrations of 1 mg/ml Nitta et al, 2002;Voravuthikunchai and Kitpipit, 2005).…”
Section: Discussionsupporting
confidence: 48%
“…Drug-resistant bacterial infection treatment has been stimulated by investigations on natural compounds as alternative medicine (Abu-Shanab et al, 2004;Adwan and Mhanna, 2008;Denis et al, 2009). In the present study, analyses of growth inhibition activity performed by using the well diffusion method showed that all the tested plants, which are commonly used by traditional medical practitioners, exhibited moderate activity against clinical isolates of bacterial strains at extract concentrations of 1 mg/ml Nitta et al, 2002;Voravuthikunchai and Kitpipit, 2005).…”
Section: Discussionsupporting
confidence: 48%
“…26,27 The epidemiology of CC239 MRSA stands in stark contrast. Patients with CC239 MRSA were younger and the median time for recovery of CC239 was nine days after admission.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…MDRO are regarded as a potentially serious threat to elderly people living in long-term care facilities (LTCFs). Although various studies on the prevalence of MRSA in LTCFs in Germany [7][8][9][10][11][12][13] and other European countries [14][15][16][17][18][19][20][21][22][23][24][25] have been published (< 1% in the Netherlands and Sweden, > 20% in Ireland and the United Kingdom (UK)), studies on the prevalence of MRGN such as extended-spectrum betalactamase (ESBL)-producing Enterobacteriaceae and vancomycin-resistant enterococci (VRE) among nursing home residents in German and in European LTCFs are scarce [7,14,24,26,27]. Although an increasing trend in the occurrence of ESBL-producing Enterobacteriaceae and even CRO is found in hospitals all over Europe [1,3,28,29], a lack of knowledge on multidrug-resistant organisms (MDRO) in nursing homes has to be stated.…”
Section: Introductionmentioning
confidence: 99%